PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM UPAYA MEMBENTUK PRIBADI MUSLIM PESERTA DIDIK DI SMA NEGERI 7 JENEPONTO - K, Munawir (Inspiratif Pendidikan, 2023)
This study aims to determine the role and efforts of Islamic Religious Education teachers in shaping the Muslim personality of students at SMA Negeri 7 Jeneponto and to find out the supporting and inhibiting factors of Islamic Religious Education teachers in shaping the Muslim personality of students at SMA Negeri 7 Jeneponto. This type of research is Qualitative. The research approach used is the phenomenological approach and the psychology of religion approach. Data collection methods used are observation, interviews and documentation. The data sources in this study were Islamic Religious Education teachers, school principals and students at SMA Negeri 7 Jeneponto, as well as other sources of information such as school archives, books, journals and pictures or documents related to the matter being studied. The results showed: (1) The role of the Islamic Religious Education teacher in shaping the Muslim personality of students at SMA Negeri 7 Jeneponto, namely: the teacher as an educator, the teacher as a teacher, the teacher as a guide, the teacher as a role model and the teacher as an adviser. Efforts made by Islamic Religious Education teachers in shaping the Muslim personality of students, namely by holding religious activities, in the form of midday prayers, Duha in congregation, and Al-Qur'an literacy. Educate students to always behave well to anyone and reprimand students who behave badly, teach children about religion such as how to read the Koran properly and correctly, provide guidance to students in reading and studying the contents or the meaning and content of the Qur'an, giving examples of good morals and advising students who behave badly, (2) Supporting factors for Islamic Religious Education teachers in shaping Muslim students' personalities: Availability of facilities and infrastructure, activities religious activities, there are positive responses from students, there is support from the principal, there is cooperation from fellow teachers and there is awareness from students to always improve themselves. Factors inhibiting Islamic Religious Education teachers in shaping Muslim students' personalities: Very limited time, lack of awareness and motivation from students and lack of religious education from parents.